2017
DOI: 10.1126/science.aal4671
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic transcription and waves of gene reactivation during mitotic exit

Abstract: Although the genome is generally thought to be transcriptionally silent during mitosis, technical limitations have prevented sensitive mapping of transcription during mitosis and mitotic exit. Thus, the means by which the interphase expression pattern is transduced to daughter cells have been unclear. We used 5-ethynyluridine to pulse-label transcripts during mitosis and mitotic exit and find that many genes exhibit transcription during mitosis, as confirmed by FITC-UTP labeling, RNA FISH, and RT-qPCR. The fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

28
305
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 223 publications
(335 citation statements)
references
References 37 publications
28
305
2
Order By: Relevance
“…If the entirety of the mitotic signal was due to an interphase population, then we would expect the relative rank of genes within this population to be identical to that of the asynchronous population. However, a pairwise analysis of the Spearman rank correlation coefficient of all mitotic and asynchronous replicates indicated that the two populations were distinct (Palozola et al 2017). From these studies and other controls (Palozola et al 2017) we conclude that mitosis is not a period of transcriptional silence, as has long been considered the case.…”
Section: Mitotic Transcriptionmentioning
confidence: 82%
See 4 more Smart Citations
“…If the entirety of the mitotic signal was due to an interphase population, then we would expect the relative rank of genes within this population to be identical to that of the asynchronous population. However, a pairwise analysis of the Spearman rank correlation coefficient of all mitotic and asynchronous replicates indicated that the two populations were distinct (Palozola et al 2017). From these studies and other controls (Palozola et al 2017) we conclude that mitosis is not a period of transcriptional silence, as has long been considered the case.…”
Section: Mitotic Transcriptionmentioning
confidence: 82%
“…Of these, 8074 were reproducibly expressed among all three mitotic replicates, accounting for 28% of the genes expressed in an asynchronous population. However, the transcriptome was expressed much lower in mitotic than in asynchronous cells, with a fivefold mean decrement in transcript levels (Palozola et al 2017). It is important to note that this low-level transcription is not purely the result of the ∼3% contaminating interphase cells in the mitotic population.…”
Section: Mitotic Transcriptionmentioning
confidence: 99%
See 3 more Smart Citations